Intervensi Spiritual Emotional Freedom Technique Untuk Menurunkan Gangguan Stres Pasca Trauma Erupsi Gunung Merapi - Elyusra Ulfa (Journal of Educational, Health and Community Psychology, 2013)
AbstractThe research objective is to examines the influence of Spiritual Emotional Freedom technique intervention to reduce PTSD of adolescent survivors of volcanic eruption. Subjects were 22 adolescent survivors of volcanic eruption, happened in 2010 in Yogyakarta and Central Java. Subjects were selected with random assignment and measured by using post traumatic stress disorder scale (adapted and modified from the Impact of Event Scale-Revised-IES-R). The subject is divided into two groups of experimental and control group, each group consisted of 11 people. The research design is pretest posttest control group design. Subject were treated by spiritual emotional freedom technique intervention (spirituality, like prayer and acceptance and energy psychology) with three technique, set-up, tune-in and tapping. The results showed that spiritual emotional freedom technique intervention can reduce PTSD of adolescent survivors of volcanic eruption.Â Key words: spiritual emotional freedom technique intervention, post traumatic stress disorder, adolescent survivors of volcanic eruption.